(untitled) (Journal of Institute of Medicine Nepal, 2011)
Introduction: Soft tissue tumors represent diagnostic challenge to general practicing pathologists because of overlap in morphologic features. The usual approach is to diagnose by presumed cell lineage. A major utility of immunohistochemistry is to identify a tumor being mesenchymal or nonmesenchymal and once mesenchymal lineage has been confirmed, histologic sub typing according to specific lineage may be achieved with help of lineage specific markers. Methods: The objective of this study was to analyse different types of soft tissue malignancies according to their type, site and age distribution, discuss the difficulties faced during morphologic examination and review the literature for role of ancillary techniques, particularly immunohistochemistry in diagnosing soft tissue sarcomas.All soft tissue malignancies reported from Tribhuvan University Teaching Hospital in three years period from April 2008 to March 2010 were included in the study. Results: Total 87 soft tissue malignancies were reported during study period. Most of these patients (58.6%) were male and the rest were female. These malignancies were found in all age groups. Youngest patient was newborn who was born with tongue mass and biopsy was performed on 13th day of life. However maximum numbers of tumors (41.4%) were seen in first two decades of life. Head and neck was the most common site .Rhabdomyosarcoma was the most common diagnosis. In 20 cases (23%) a definite opinion was not possible and vague terms like sarcoma, small round cell tumor, spindle cell malignancy, vascular tumor “likely” were used. Immunohistochemistry was advised in these cases. Conclusions: Only light microscopic examination of hematoxylin and eosin stained slide not sufficient at all times because there is morphologic overlap of soft tissue sarcomas with each other and with carcinomas and melanomas. Though immunohistochemistry is not a substitute for skilled interpretation of routinely stained slides but prove helpful to reach a more definite diagnosis. Keywords: Immunohistichemistry; sarcoma; soft tissue DOI: http://dx.doi.org/10.3126/joim.v32i2.4941 Journal of Institute of Medicine, August, 2010; 32: 26-29